Semiotic Analysis of Patriotism in Hacksaw Ridge and Letters from Iwo Jima Movie - Mohamad Gibran Syaeful Rahman (Universitas Galuh, 2023)
Each country have different meaning of Patriotism. Therefore, this research comparing on the movie of Hacksaw Ridge and Letters from Iwo Jima since both of the movies showed differences perspective of patriotism since both of them from different culture. The research aimed at revealing the semiotic of patriotism in Hacksaw Ridge and Letters from Iwo Jima movie. This research is based on Roland Barthes semiotic theory, Nathanson patriotism theory and Joana Japanese patriotism. The qualitative method was employed by analyzing the symbols that indicate the act of patriotism found in the movie. The research used a descriptive design. The object of the research is the character and the background of the set was taken. Document analysis was used as the instrument in order to get the valid data. There are 57 data that took from the 10 scenes from each movies to symbolize the Dennotative, Connotative and Myth. From the analysis, three types of symbols were found that showed by the character or the background set. They were data 33,33% of Dennotative (10 occurrences), 33,33% of Connotative(10 occurrences) and 33,33% of Myth(10 occurrences) in Hacksaw Ridge movie. As for the Letters From Iwo Jima, 37% of Dennotative (10 occurrences), 37% of Connotative (10 occurrences) and 26% of Myth (7 occurrrences). The data semiotic Analysis were based on Roland Barthes theory